1978
DOI: 10.1002/maco.19780290802
|View full text |Cite
|
Sign up to set email alerts
|

Zur Inhibition der Eisenkorrosion in wäßrigen Lösungen

Abstract: Kurzfassung Die Inhibitionswirkungen von Propan(1,3)-biphosphonsaure und Hexan(l,6)-biphosphonsaure auf die Korrosion von hochreinem Eisen (polykristallin, rekristallisiert) in wagrigen Sulfatlosungen im Bereich 4 < pH < 6 in Abwesenheit und Gegenwart von Sauerstoff wurde bei T = 298 K untersucht. Es wurden stationare und zyklisch voltammetrische Messungen an rotierenden Elektroden durchgefiihrt. Beide Substanzen wirken als Grenzflacheninhibitoren. Die erhaltenen Schutzwerte am Korrosionspotential sind jedoch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…8 for 3.5h and for longer exposure times, and the model in Eq. [6]. These results cast some doubt on the experimental data and the model proposed by Bonnel et al (24) and Duprat et al (25), who reported the occurrence of a second time constant at low frequencies (<0.1 Hz) for a carbon steel rotating disk electrode in 3% NaC1.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…8 for 3.5h and for longer exposure times, and the model in Eq. [6]. These results cast some doubt on the experimental data and the model proposed by Bonnel et al (24) and Duprat et al (25), who reported the occurrence of a second time constant at low frequencies (<0.1 Hz) for a carbon steel rotating disk electrode in 3% NaC1.…”
Section: Resultsmentioning
confidence: 85%
“…The impedance spectra for the inhibitor-free solution and for the presence of NaNO:, or inhibitor B conform to the model in Eq. [6]. The effect of the inhibitors is seen in the increase of Rp (low frequency limit of the impedance ]2~) and a lowering of the capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…In this practically important case both metal dissolution and oxygen reduction processes are strongly influenced by a 3-D surface inhomogeneity consisting of a porous oxidic layer, the formation of which depends on the corrosion time and the hydrodynamic conditions. 2-and 3-D surface layers may act as interface and interphase corrosion inhibitors, respectively (7,(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…In neutral oxygen-containing solutions. the iron dissolution is strongly inhibited by the formation of a porous oxide layer, which behaves like a membrane [91 controlling the oxygen diffusion [10][11][12]. Iron dissolution firstly occurs in the so-called prepassive range, however is shifted, depending on time, into the active range [ 12).…”
Section: Introductionmentioning
confidence: 99%